Comparison of users of an HIV/syphilis screening community-based mobile van and traditional voluntary counselling and testing sites in Guatemala. Issue 2 (11th November 2010) - Lahuerta, Maria; Sabidó, Meritxell; Giardina, Federica; Hernández, Gabriela; Palacios, Juan Fernando; Ortiz, Rudy; Fernández, Victor Hugo; Casabona, Jordi; ,
Abstract : Objectives: The use of a mobile van (MV) for screening for HIV and other sexually transmitted infections (STIs) is effective at reaching at-risk populations. The aim of this study was to compare behaviour characteristics and HIV and syphilis prevalence between subjects tested at a MV offering voluntary counselling and testing and those tested at three STI clinics in Guatemala. Methods: Over 28 months, female sex workers (FSWs), men who have sex with men/transgenders (MSM/TG), and people not reporting being a member of a risk group (NR) were offered HIV and syphilis rapid tests and interviewed about their sociodemographic and risk behaviour. Results: 2874 subjects were tested (MV, 1336 (46%); clinics, 1538 (54%)). The MV screened 73% of FSWs and 73% of the MSM/TG, and detected 19% of HIV and 69% of syphilis cases. HIV prevalence was significantly higher (p<0.001) at the STI clinics than at the MV for both NR and MSM/TG groups (NR, 7% vs 1%; MSM/TG, 8% vs 1%, respectively). A significantly higher proportion of MSM/TG screened at the STI clinic reported having had a prior HIV test (MV, 21%; clinics, 41%; p<0.001), whereas more FSWs tested in the MV reported having multiple partners and using condoms during their last sexual intercourse. Conclusions: The higher prevalence of HIV and syphilis at the STI clinics suggests that they successfully identified high-risk subjects. In particular, the NR group showed higher than expected HIV and syphilis prevalence. Innovative approaches such as the use of a MV helped to increase access to other hard-to-reach groups such as MSM/TG and FSWs.